A PHENOMENOLOGICAL STUDY OF OBSTETRICIANS’ LIVED EXPERIENCES IN MANAGING HIGH-RISK OBSTETRIC CASES - Jadoon, Humaira; Khan, Attiya bibi; Islam, Ansa; Ahmed Khan, Salar; Khan, Maria; Sarfaraz, Junaid (Journal of Ayub Medical College Abbottabad, 2026)
Background: This phenomenological study examines the experiences of obstetricians handling high-risk cases, such as postpartum hemorrhage, antepartum hemorrhage, uterine rupture, and sepsis, in a resource-limited tertiary care hospital in Pakistan. Method: Through questionnaires (open ended questions) with 10 obstetricians, the study identifies four key themes: emotional challenges and psychological stress, systemic resource shortages, professional resilience and coping strategies, and recommendations for institutional support. Results: Obstetricians reported a heavy emotional burden, worsened by their frequent encounters with maternal and neonatal deaths, and a lack of access to mental health services. Systemic issues, such as delays in lab tests, not enough ICU beds, bureaucratic obstacles, and inadequate blood bank support, often delayed care and increased clinical risks. Despite these difficulties, clinicians used informal coping methods like peer support, teamwork, and following protocols. Participants highlighted the need for non-punitive feedback systems, regular emergency drills, decentralizing low-risk deliveries, and integrating mental health services for staff. Conclusion: The study employs Colaizzi’s method to analyze the narratives, showing the complex, emotional, and systemic aspects of maternal care that are often missed in quantitative research. The findings stress the urgent need to make healthcare systems more compassionate by recognizing provider stress and implementing structural, psychological, and procedural changes. This research deepens the understanding of obstetric practices in low-resource settings and provides insights for policies aimed at improving maternal outcomes and clinician well-being. While the study is limited by being conducted at one site, it sets the stage for further exploration into healthcare professionals’ experiences in low-to-middle-income countries.